Crafting Mass Partisanship at the Grass Roots. Issue 4 (26th March 2014) - Samuels, David; Zucco, Cesar
<x content-type="archive" xml:space="preserve">Abstract</x> What are the sources of mass partisanship? The focus of this article is on the role of party organizational strategies in Brazil, where sociological cleavages are weak. All Brazilian parties post electoral gains by opening local branch offices, but only the Workers' Party (PT) manages to win voters' hearts and minds, cultivating mass partisan identification. This follows from its deliberate effort to use its local party organization to reach out to organized civil society – to 'mobilize the organized.' Results further indicate that the PT only gains partisan identifiers where civil society is organizationally dense. Together, this suggests that party strategy to cultivate partisanship is insufficient: pre-existing organizational networks must exist in civil society, meaning that 'top-down' and 'bottom-up' strategies are two sides of the same coin.